2017
DOI: 10.1007/s10803-017-3057-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk Factors for the Development of Self-Injurious Behavior among Infants at Risk for Autism Spectrum Disorder

Abstract: Prevalence of self-injurious behavior (SIB) is as high as 50% among children with autism spectrum disorder (ASD). Identification of risk factors for the development of SIB is critical to early intervention and prevention. However, there is little empirical research utilizing a prospective design to identify early risk factors for SIB. The purpose of this study was to evaluate behavioral characteristics predicting SIB at age 2 years among 235 infants at high familial risk for ASD. Logistic regression results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…Fodstad, Matson, & Rojahn (2012) found that in a sample of very young children (around 10–12 months) with IDD, approximately 18.3% were engaging in SIB, including milder forms of eye poking, self-hitting, and head banging. Other researchers have found similar data on early SIB indicating that approximately 15 – 30% of children under 5 years of age with IDD exhibit early forms of SIB (Berkson, Tupa, & Sherman, 2001; Dimian et al, 2017; Schroeder et al, 2014). Thus, even very early in life, SIB occurs in children with IDD.…”
supporting
confidence: 56%
“…Fodstad, Matson, & Rojahn (2012) found that in a sample of very young children (around 10–12 months) with IDD, approximately 18.3% were engaging in SIB, including milder forms of eye poking, self-hitting, and head banging. Other researchers have found similar data on early SIB indicating that approximately 15 – 30% of children under 5 years of age with IDD exhibit early forms of SIB (Berkson, Tupa, & Sherman, 2001; Dimian et al, 2017; Schroeder et al, 2014). Thus, even very early in life, SIB occurs in children with IDD.…”
supporting
confidence: 56%
“…Current research demonstrates persistence of SIB across the life span [12], with one review suggesting SIB is both common and stable over time for individuals with autism [13]. Further studies also highlight persistence in adolescents and adults without autism and with broader developmental disabilities [14,15]; however, further research is needed to extend this evidence.…”
Section: Introductionmentioning
confidence: 96%
“…There exist a number of informant-and self-report instruments that characterize precisely this type of variability in older children and adults (Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001;, but fewer that have been designed explicitly to characterize the dimensionality of autistic traits/features in toddlers and preschool-aged children, periods vital to understanding the early manifestation of the disorder. The Repetitive Behavior Scales for Early Childhood (RBS-EC; Wolff, Boyd, & Elison, 2016) was designed to overcome two shortcomings of the widely used Repetitive Behavior Scales-Revised (RBS-R; Bodfish, Symons, Parker, & Lewis, 2000;Lam & Aman, 2007;Mirenda et al, 2010), despite the latter's utility in differentiating 12-and 24-month-old high-risk infant siblings of children with autism who subsequently received a diagnosis themselves (Dimian et al, 2017;Wolff et al, 2014). Namely, the RBS-EC was designed to (a) capture variability across the typical-to-atypical continuum and (b) incorporate developmentally appropriate items for young children, nominally between 6 months and 8 years of age.…”
mentioning
confidence: 99%